Forms of Exile in Jewish Literature and Thought : Twentieth-Century Central Europe and Migration to America. - Volková, Bronislava. (Academic Studies Press, 2021)
This volume deals with the concept of exile onmany levels--from the literal to the metaphorical--combining analyses ofpredominantly Jewish authors of Central Europe. The concept and forms of exileare analyzed from many different points of view and great importance is devotedespecially to forms of inner exile.